A bibliometric analysis of cardiotoxicity in cancer radiotherapy - Che, Mengting; Duan, Yuanqiong; Yin, Rutie (Frontiers in Oncology, 2024)
Radiotherapy, a primary treatment for malignant cancer, presents significant clinical challenges globally due to its associated adverse effects, especially with the increased survival rates of cancer patients. Radiation induced heart disease (RIHD) significantly impacts the long-term survival and quality of life of cancer survivors as one of the most devastating consequences. Quite a few studies have been conducted on preclinical and clinical trials of RIHD, showing promising success to some extent. However, no researchers have performed a comprehensive bibliometric study so far. This study attempts to gain a deeper understanding of the focal points and patterns in RIHD research and to pinpoint prospective new research avenues using bibliometrics. After collecting all the data, a total of 1554 documents were categorized and analyzed using visualization tools like CiteSpace and VOS viewer. In 2013, there was a significant rise in the number of linked publications, with the majority of authors being from the USA, according to the statistics. Among all the journals, INTERNATIONAL JOURNAL OF RADIATION ONCOLOGY BIOLOGY PHYSICS published the most relevant papers. High-frequency keywords in the analysis include risk factors, cancer types, heart disease, survival, trials, proton therapy (PT), ect. Future research on RIHD will mostly focus on thoracic cancer, whose exact cause is yet unknown, with preclinical trials playing an important role. Preventing, consistently monitoring, promptly diagnosing, and timely treating are crucial to decreasing RIHD and extending the life expectancy of cancer survivors.